Temporal-spatial distribution of oceanic vertical deflections determined by TOPEX/Poseidon and Jason-1/2 missions - Guo, Jin Yun; Shen, Yi; Zhang, Kaihua; Liu, Xin; Kong, Qiaoli; Xie, Feifei (Earth Sciences Research Journal, 2016)
Deflections of the Vertical (DOV) are essential data in the geodetic observation reduce, the earth gravity field and geoid model refinement, and the mass earth change. The meridional and prime vertical components of global oceanic DOVs are estimated from altimetry data of TOPEX/Poseidon, Jason-1, and Jason-2, through 1992 to 2013 with the crossover method, to analyze the temporal-spatial distribution of marine DOVs. Comparing with the EGM2008-modelled DOVs, precisions of meridional and prime vertical components can be up to 0.98” and 1.02”, respectively. The time series of annual mean DOVs from 1992 to 2013 are studied to get the annual variation law. Annual changes of meridional and prime vertical components are small over most oceans. But the annual changes are significant over oceans with large submarine topography undulations. The spatial distribution of oceanic DOVs is also analyzed. The absolute DOVs over oceans around lands, islands, and large oceanic trenches are greater than those over the other oceans. The meridional and prime vertical components are consistent with the longitude and latitude directions, respectively. Resumen Las Desviaciones de la Vertical (DOV, del inglés Deflections of the Vertical) son información esencial en la simplificación de la observación geodésica, el campo gravitatorio terrestre y el perfeccionamiento del modelo geoide, y el cambio de la masa terrestre. Se estimaron los componentes meridional y principal vertical de las desviaciones de la vertical oceánica global con la información altimétrica de TOPEX/Poseidón, Jason 1 y Jason 2, de 1992 a 2013, con un método de cruce para analizar la distribución espacio-temporal de las desviaciones de la vertical marinas. Comparadas con las desviaciones de la vertical obtenidas con el modelo EGM2008 (Modelo de Gravitación de la Tierra), la precisión de los componentes meridional y principal vertical puede aumentarse 0.98" y 1.02", respectivamente. Se estudiaron las series temporales de la media anual de las desviaciones de la vertical desde 1992 a 2013 para obtener la ley anual de variación. Los cambios anuales de los componentes meridional y principal vertical son muy pequeñas en la mayoría de los océanos. Sin embargo, los cambios anuales son mayores en aquellos océanos con una topografía submarina de grandes ondulaciones. También se analizó la distribución espacial de las desviaciones de la vertical oceánicas. Las desviaciones de la vertical absolutas alrededor de los continentes, islas y fosas oceánicas mayores son superiores que aquellas sobre los otros océanos. Los componentes meridional y vertical principal son consistentes con las direcciones de la longitud y la latitud, respectivamente.